COL18A1 genotypic associations with endostatin levels and clinical features in pulmonary arterial hypertension: a quantitative trait association study. Issue 2 (27th June 2022) - Simpson, Catherine E.; Griffiths, Megan; Yang, Jun; Nies, Melanie K.; Vaidya, Dhananjay; Brandal, Stephanie; Martin, Lisa J.; Pauciulo, Michael W.; Lutz, Katie A.; Coleman, Anna W.; Austin, Eric D.; Ivy, D. Dunbar; et al.
Endostatin (ES) is a circulating peptide derived from collagen XVIII alpha 1 (COL18A1) known to inhibit angiogenesis [1, 2]. Decreased angiogenesis is a feature of pulmonary arterial hypertension (PAH) in animal models [3] and human subjects [4]. Our group has reported strong associations between circulating ES levels and haemodynamics and survival in PAH [5–7]. We have also reported that a missense variant in COL18A1, which encodes ES, confers lower ES and longer survival, suggesting that variation within the gene contributes to circulating levels [5]. In the current study, we assessed COL18A1 variant associations with clinical phenotypes and outcomes, including COL18A1 associations with circulating ES levels, in a large, multicentre PAH cohort in which we previously investigated ES as a prognostic biomarker [6]. Variation around the COL18A1 gene, which encodes the angiostatic peptide endostatin, may influence disease heterogeneity in pulmonary arterial hypertension https://bit.ly/3shXrNR